БАРКАМОЛ АВЛОДНИ ШАКЛЛАНТИРИШДА МАЪНАВИЙ МЕРОСДАН ФОЙДАЛАНИШ МАСАЛАЛАРИ - Камолова, К. (SCIENCE and SOCIETY, 2020)
The article discusses the role and significance of spiritual heritage in the upbringing of a highly spiritual and harmonious generation, the issues of its positive use and the attention paid to them today.
Keywords: spiritual heritage; high spirituality; perfection; "Avesto"; thinker